Two new cyclobutane derivatives of thiazolidin-4-ones: Synthesis, spectroscopic characterization, DFT quantum chemical calculations and determination of protonation constants - Ekici, Oner; Cukurovali, Alaaddin (Elsevier, 2025)
In the first stage of this study, 2-((4-(4-(3-methyl-3-phenylcyclobutyl)thiazol-2-yl)imino)thiazolidin-4-one (compound 1) and 2-((4-(3-(2,5-dimethylphenyl)-3-methylcyclobutyl)thiazol-2-yl)imino)thiazolidin-4-one (compound 2) were synthesized, characterized using FT-IR and NMR methods, and a combination of experimental and theoretical studies of the title compounds was performed. With the aid of the 6-311+G(d,p) basis set, all theoretical computations were performed using the density functional theory (DFT) B3LYP approach. The GIAO approximation was used to compute the chemical shifts of 1H and 13C NMR. Theoretical calculations provide detailed information on chemical activity and molecular properties by determining electrophilic and nucleophilic properties. Accordingly, global chemical activity descriptors (FMOs, hardness, and softness parameters) were investigated, natural bond orbital (NBO) analyses were performed, thermodynamic properties at different temperatures were calculated, and the related relationships with temperature were obtained. The experimental and calculated NMR data presented consistent results for both compounds. R2 values for the 1H NMR and 13C NMR of compound 1 are 0.9914 and 0.9988, respectively. For the second compound, 2, these values are 0.9957 and 0.9962, respectively. In the second stage, the acid-base equilibria of title compounds containing cyclobutane, thiazole, and thiazolidinone functional groups were investigated potentiometrically in 60 % dioxane-water media at room temperature and constant ionic strength. The values of the protonation constants determined in this study, logKNH(1) and logKNH(2), are related to the protonation of the azomethine nitrogen atom and the nitrogen atom on the thiazole ring, respectively. The sum of these values is the total protonation value of title compounds. The total protonation constants for compounds 1 and 2 are 10.59 and 10.58, respectively.
Keywords: Cyclobutane; Thiazole; Thiazolidinone; Density functional theory (DFT); Protonation constants